Industri pabrik perhutani sebagai strategi pengurangan pengangguran di Kediri - Fitriani, Ninis (Maliki Interdisciplinary Journal, 2024)
Unemployment is the reason why Indonesia still has a lot of poverty. Because many job vacancies have many unreasonable requirements, this causes unemployment to increase and burden the country. The form of reducing unemployment is of course by opening up employment opportunities such as wood factories which have long working periods and the requirements prioritize physical abilities. Timber factories play a role in reducing unemployment in Indonesia, as evidenced by the high level of job absorption and the ability to employ people from various groups. One example is in Kediri, where the establishment of a factory is able to absorb the workforce around it and is able to reduce unemployment. Perhutani Factory Perhutani, a state-owned timber company, is an important pillar of Indonesia's rural economy. Its presence opens up employment opportunities for local people, which significantly reduces unemployment and improves living standards. More than that, Perhutani also contributes to alleviating poverty through various empowerment and economic development programs in the surrounding area.